Strain engineering in perovskite solar cells and its impacts on carrier dynamics - Cheng Zhu (Nature Portfolio, 2019)
The residual strains in the mixed halide perovskite thin films and their effects on the solar cell devices are less understood. Here Zhu et al. study the impact of the gradient in-plane strain on the carrier dynamics of the strained perovskite films and optimize the device efficiency.